Automatic Inspection of Cod (Gadus Morhua L.) Fillets by Hyperspectral Imaging - Sivertsen, Agnar Holten (Universitetet i Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. A. H. Sivertsen, C. Chu, L. Wang, F. Godtliebsen, K. Heia and H. Nilsen: 'Ridge detection with application to automatic fish fillet inspection', Journal of Food Engineering (2009), vol. 90, pp. 317–324. Available at http://dx.doi.org/10.1016/j.jfoodeng.2008.06.035 2. A. H. Sivertsen, K. Heia, S. K. Stormo, E. Elvevoll and H. Nilsen: 'Automatic nematode detection in cod fillets (Gadus Morhua) by transillumination hyperspectral imaging', Journal of Food Science (2011), vol. 76, pp. 77-83. Available at http://dx.doi.org/10.1111/j.1750-3841.2010.01928.x 3. A. H. Sivertsen, K. Heia, K. Hindberg and F. Godtliebsen: 'Automatic nematode detection in cod fillets (Gadus Morhua L.) by hyperspectral imaging' Journal of Food Science (2011), Volume 76, Issue 1, pages S77–S8. Available at http://dx.doi.org/10.1111/j.1750-3841.2010.01928.x 4. A. H. Sivertsen, T. Kimiya and K. Heia: 'Automatic freshness assessment of cod (Gadus morhua) fillets by VIS/NIR spectroscopy', Journal of Food Engineering (2011), vol 103, pp. 317-323. Available at http://dx.doi.org/10.1016/j.jfoodeng.2010.10.030 The manual trimming and inspection of cod fillets by candling, is considered the bottleneck of cod fillet processing. The operation is both labour intensive and expensive, reported to account for as much as 50 % of the cost with cod fillet production. Due to the high labour costs in Norway, it is of great interest for the industry to optimize this process. In this work a hyperspectral imaging system has been developed, capable of inspecting cod fillets, with or without skin, at a conveyor belt speed of 400 mm/seconds, corresponding to the industrial processing speed of one fish per second. The system is designed as proof of concept, and the algorithms are not implemented to be run in real time. A method for segmenting a cod fillet image into the respective parts: loin, belly and tail, using the centerline as a reference system, has been developed. The method is useful for selecting ...